2015
DOI: 10.1188/15.onf.552-554
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Reporting Items for Systematic Reviews and Meta-Analyses

Abstract: This article describes the Preferred Reporting Items of Systematic Reviews and Meta-Analyses (PRISMA) guidelines that are intended to help authors improve the reporting of systematic reviews and meta-analyses, illustrating with examples from the Oncology Nursing Society journals and Putting Evidence Into Practice resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(75 citation statements)
references
References 11 publications
0
69
0
Order By: Relevance
“…Relevant articles referenced in these publications were obtained and the references of identified studies were searched to identify any further studies. A flow chart of the literature searches according to PRISMA guidelines20 is shown in figure 1A and B.…”
Section: Methodsmentioning
confidence: 99%
“…Relevant articles referenced in these publications were obtained and the references of identified studies were searched to identify any further studies. A flow chart of the literature searches according to PRISMA guidelines20 is shown in figure 1A and B.…”
Section: Methodsmentioning
confidence: 99%
“…A manual search for other potential articles beyond the abovementioned databases was also performed. A flow chart of the literature searches according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines27 is shown in figure 1. Only Chinese and English papers were included.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement carefully in the whole process of this analysis [35]. By merging ORs with 95% CI, we evaluated the association between TNF-α polymorphisms and NONFH risks.…”
Section: Discussionmentioning
confidence: 99%